The Impact of Corporate Social Responsibility On Consumer Loyalty: A Mediation Analysis of Consumer Trust and Satisfaction - Annisa Fajri; Haerudin; Abdul Aziz Agbo (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Corporate Social Responsibility (CSR) has been identified as a critical factor influencing consumer loyalty, but its mechanisms remain underexplored, especially regarding consumer trust and satisfaction as mediators.Purpose: This study examines the mediating roles of consumer trust and satisfaction in the relationship between CSR and consumer loyalty.Design/methodology/approach: A sample of 100 active students from the Management Study Program at Universitas Muhammadiyah Semarang was surveyed. SmartPLS 3.0 was used to analyze the data and assess convergent validity, reliability, and hypothesis testing.Findings/Result: CSR positively and significantly affects consumer loyalty, mediated by consumer trust and satisfaction. Conclusion: CSR initiatives improve consumer trust and satisfaction, which in turn enhances loyalty.Originality/value (State of the art): This study contributes to CSR literature by providing empirical evidence from an Indonesian context, highlighting the critical mediating roles of trust and satisfaction. Keywords: corporate social responsibility; costumer trust; customer satisfaction; consumer loyalty; stakeholder theory